Complement activation predicts adverse pregnancy outcome in patients with systemic lupus erythematosus and/or antiphospholipid antibodies. Issue 4 (25th January 2018) - Kim, Mimi Y; Guerra, Marta M; Kaplowitz, Elianna; Laskin, Carl A; Petri, Michelle; Branch, D Ware; Lockshin, Michael D; Sammaritano, Lisa R; Merrill, Joan T; Porter, T Flint; Sawitzke, Allen; Lynch, Anne M; et al.
Abstract : Objective: Studies in mouse models implicate complement activation as a causative factor in adverse pregnancy outcomes (APOs). We investigated whether activation of complement early in pregnancy predicts APOs in women with systemic lupus erythematosus (SLE) and/or antiphospholipid (aPL) antibodies. Methods: The PROMISSE Study enrolled pregnant women with SLE and/or aPL antibodies (n=487) and pregnant healthy controls (n=204) at <12 weeks gestation and evaluated them monthly. APOs were: fetal/neonatal death, preterm delivery <36 weeks because of placental insufficiency or preeclampsia and/or growth restriction <5th percentile. Complement activation products were measured on serial blood samples obtained at each monthly visit. Results: APO occurred in 20.5% of SLE and/or aPL pregnancies. As early as 12–15 weeks, levels of Bb and sC5b-9 were significantly higher in patients with APOs and remained elevated through 31 weeks compared with those with normal outcomes. Moreover, Bb and sC5b-9 were significantly higher in patients with SLE and/or aPL without APOs compared with healthy controls. In logistic regression analyses, Bb and sC5b-9 at 12–15 weeks remained significantly associated with APO (ORadj =1.41 per SD increase; 95% CI 1.06 to 1.89; P=0.019 and ORadj =1.37 per SD increase; 95% CI 1.05 to 1.80; P=0.022, respectively) after controlling for demographic and clinical risk factors for APOs in PROMISSE. When analyses were restricted to patients with aPL (n=161), associations between Bb at 12–15 weeks and APOs became stronger (ORadj =2.01 per SD increase; 95% CI 1.16 to 3.49; P=0.013). Conclusion: In pregnant patients with SLE and/or aPL, increased Bb and sC5b-9 detectable early in pregnancy are strongly predictive of APOs and support activation of complement, particularly the alternative pathway, as a contributor to APOs.